PENGALAMAN KOMUNIKASI ORGANIZATION PUBLIC RELATIONSHIP DALAM MEMBERIKAN KUALITAS LAYANAN OPERASI SAR DI BASARNAS - Dio Putra; Emeraldy Chatra; Elva Ronaning Roem (Ensiklopedia of Journal, 2021)
Connection interpersonal communication or between personal is communication carried out for understand how individual other act. On for example is communication carried out in a SAR operations between Member Basarnas with Public on moment happening disaster nature. Communication this really important to achieve maximum results in rescue victim disaster nature. Destination study this is for knowing experience verbal and nonverbal communication public relations Basarnas to community, for knowing emerging concepts Jambi Basarnas about experience communication organization public relations in increase quality service SAR operations at the Jambi Basarnas, to knowing meaning  Jambi Basarnas about experience communication organization public relations in increase quality service SAR operations at the Jambi Basarnas. Methodology in study this is through approach qualitative with studies phenomenology. Research data obtained through Interview deep and informant totaling 3 people. Based on analysis carried out on Interview deep experience public relations verbal communication in give quality service SAR operations at the Jambi Basarnas found in study is vocabulary (use of language), racing (speed), short and clear as well as intonation. Experience public relations nonverbal communication in give quality service SAR operations at the Jambi Basarnas found in study is gestural message, touch, guard distance and motion cue. Concepts raised about experience communication organization public relations in increase quality service SAR operations at the Jambi Basarnas were found in study is attitude positive, open, attitude support, equality and empathy. Meaning experience communication organization public relations in increase quality service SAR operations at the Jambi Basarnas were found in study is integrity, loyalty, competent, consistency and openness